Perceptions of Food Safety Risk, Post-harvest Practices and Intertemporal Staple Crop Allocation: Evidence from Maize in Nepal. - Armah, Ralph. (Tufts University. Tisch Library., 2020)
This posters main objective is to examine how self-state perceived awareness of food safety risks affects farmers' storage decision.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy